The Influence of Perceived Autonomy Support on Physical Activity Among High School Students: The Mediating Roles of Basic Psychological Needs - Zhou Wanwan; Ahmad Zamri Khairani (Behavioral Sciences)
Parental and peer support has been documented as an important factor in physical activities among high school students. Likewise, coach support has an important impact on physical activity among high school students. Meanwhile, many studies show that basic psychological needs have an essential effect on perceived autonomy and physical activity. As such, this study, using self-determination theory, aimed to explore the mediating role of basic psychological needs on physical activity among high school students in China. The Sport Climate Questionnaire, Psychological Need Satisfaction in Exercise Scale—Physical Activity, and the three-item Physical Activity Rating Scale-3 were employed to gauge responses from 736 high school students (15–18 years old). A structural equation model was employed to test the mediating effect. The researchers found a significant positive effect of perceived coach support on basic psychological need satisfaction. Basic psychological need satisfaction was also found to be a significant predictor of physical activity. Surprisingly, the results showed that perceived coach support negatively influences physical activity. As such, an indirect mediating effect is established. Basic psychological needs had an indirect mediating effect and could reduce the negative effect of coach support on physical activity engagement.